Prospects for a European welfare state: Lessons from welfare state development in six OECD-Federations - Herbert Obinger; Stephan Leibfried; Francis G. Castles (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
This paper uses the findings of a very recent major international research collaboration on the impact of federal arrangements on the development of the welfare state to explore the possibilities of progress beyond Europe's present diversity of nation-state welfare standards. These findings - based on the longterm historical experience of the OECD's oldest federations - suggest that federal arrangements tend to slow down welfare state consolidation, but that much depends on the context of historical development. The emergence of bypass mechanisms circumventing federal veto-points is located as the key to welfare progress, and the role of regulation in European integration and the special role of the ECJ as well as that of "the open method of co-ordination" are tentatively identified as possible EU bypass equivalents.
Keywords: 330; Sozialstaat; Föderalismus; Australien; Österreich; Kanada; Deutschland; Schweiz; USA